Organization of Building Plots of Mixed- Use Buildings in Light of Adapting Settlements to the Impacts of Climate Change - Jernej Červek; Matej Nikšič (Igra Ustvarjalnosti)
The impacts of climate change are increasingly evident in settlements, especially in cities and other urban areas, which poses a challenge for new approaches in urban planning. Climate change, such as rising temperatures, altered precipitation patterns with extreme weather events, changes in cloudiness and solar radiation, and an increase in the number of hot summer days, have already caused changes in climate types in Slovenia. Urban areas that are not adapted to the new conditions face negative consequences, such as flooding during heavy rainfall due to excessive soil cover and an overloaded sewage system. The soil sealing with buildings and other impermeable surfaces inhibits evapotranspiration and limits the infiltration of rainwater on natural terrain, as is otherwise possible on terrain that has direct contact with the geological base - such terrain supports water retention, runoff and infiltration and allows the planting of tall vegetation. Effective adaptation to climate change requires new urban planning approaches that include thoughtful planning of building plots. These approaches emphasize the mixing of compatible activities and the establishment of a balance between sealed and natural areas in accordance with the placement of buildings in urban space. The article presents an urban planning tool that responds to the challenges of climate change from the perspective of a quality mixing of activities in different types of buildings, from the perspective of the organization of building plots, the representation of different activities in buildings and the placement of buildings in urban settlements, densification, the provision of green spaces and improving residents' accessibility to services.